1999
DOI: 10.1099/00207713-49-1-217
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and phylogenetic characterization of a novel Lactobacillus species from human sources: description of Lactobacillus iners sp. nov.

Abstract: Eleven strains of a hitherto undescribed Gram-positive, catalase-negative, facultatively anaerobic rod-shaped bacterium from human sources and medical care products were characterized by phenotypic and molecular taxonomic methods. The phenotypic properties of the bacterium were consistent with its assignment to the genus Lactobacillus but it was readily distinguished from all currently described species of this genus by its biochemical characteristics and by SDS-PAGE analysis of its cellular proteins. Comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
91
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(103 citation statements)
references
References 12 publications
5
91
0
5
Order By: Relevance
“…Consequently, accurate genomic methods, such as ARDRA (10), are needed in order to define the Lactobacillus microbiota in the vagina. Additionally, some Lactobacillus species, such as L. iners, do not grow on Rogosa or MRS media traditionally used for lactobacillus recovery (16). This species seems to be dominant both among white (17) and black women (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, accurate genomic methods, such as ARDRA (10), are needed in order to define the Lactobacillus microbiota in the vagina. Additionally, some Lactobacillus species, such as L. iners, do not grow on Rogosa or MRS media traditionally used for lactobacillus recovery (16). This species seems to be dominant both among white (17) and black women (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, the group of organisms previously known as L. acidophilus was shown to be highly heterogeneous, and was divided subsequently into DNA homology groups A and B to form the six separate species: (14). L. jensenii and L. iners are other common lactobacilli found in the human vagina (15,16). The closely related species within the L. acidophilus complex are quite difficult and sometimes impossible to differentiate by phenotypic methods.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic studies based on the 16S rRNA gene sequence of strain Y10 suggested that this bacterium was a member of the Lactobacillus acidophilus group (van Beek & Priest, 2002). This group comprises L. acidophilus sensu stricto, Lactobacillus amylovorus, Lactobacillus crispatus, Lactobacillus gallinarum, Lactobacillus gasseri, Lactobacillus helveticus and Lactobacillus johnsonii (Johnson et al, 1980;Fujisawa et al, 1992;Gancheva et al, 1999), with three relatively recent additions: Lactobacillus amylolyticus, isolated from malt and beer wort (Bohak et al, 1998), Lactobacillus iners, associated with human sources (Falsen et al, 1999) and Lactobacillus kitasatonis, from chicken intestines (Mukai et al, 2003). In this study, we have investigated the phylogenetic relationships between the Japanese and Scottish isolates from whisky fermentations and shown that they constitute a distinct taxon within the L. acidophilus lineage, for which we propose the name Lactobacillus suntoryeus sp.…”
mentioning
confidence: 99%
“…15,16 Furthermore, the type of culture medium used for isolation of genital bacteria can bias the types of cultivatable bacteria found. 17 To avoid possible culture bias, a recent study used Multitag Pyrosequencing (MTPS) of the 16S ribosomal RNA (rRNA) gene to characterize the genital microbiota of rhesus macaques (Macaca mulatta).…”
mentioning
confidence: 99%